Developing a self‐organized tubulogenesis model of human renal proximal tubular epithelial cells in vitro. Issue 3 (16th December 2019) - Wang, Xiuli; Guo, Chengchen; Chen, Ying; Tozzi, Lorenzo; Szymkowiak, Sophia; Li, Chunmei; Kaplan, David L.
Abstract: Three‐dimensional tissue culture models which recapitulate the phenotype and function of human renal tissue have attracted significant interest as valuable tools for studying kidney development, disease pathophysiology, and nephrotoxicity. Here, a layer‐by‐layered three‐dimensional (3D) co‐culture technique was employed to bioengineer an improved human proximal tubule tissue model through incorporating human renal proximal tubule epithelial cells (RPTECs) with two types of interstitial cells on the layered extracellular matrix‐like culture matrix. The resulting cultures were characterized by their growth profile, metabolic and proliferative activity, morphological characteristics as well as their functional gene expression. Our results found that the cultures were able to enable the self‐organization of RPTECs and promote the tubule‐like structure formation in vitro. A well‐defined lumen structure and polarized expression of some key protein markers including actin, P‐gp, Na + ‐K + ‐ATPase, and SGLT2 were also observed in the 3D co‐cultures. Moreover, compared to the 3D monocultures, the tubule‐like structures formed within the 3D co‐cultures displayed more significant polarity and enhanced functional gene expression. This suggested the important role played by the renal stromal cells in supporting the tubulogenesis and differentiation of RPTECs. Thus, the 3D co‐culture model reported here would benefit bioengineering approaches toward more physiologically relevant proximal tubule tissue in vitro, providing more robust tool not only for better understanding kidney development and pathophysiology but also for drug screening for nephrotoxicity.